INVESTIGATED STRINGENT REQUIREMENTS FOR LIGHT INDUSTRY PRODUCTS AND PERMISSIBLE BURROWS OF ELECTRIC CHARGE (World Science, 2021)
In article the strict requirements imposed to products of light industry by the international EKO-TEX-100 standard are considered, characteristics of the properties of biological safety of clothes produced from textile materials and a knitted cloth are given, the question of existence of an electro statistical charge in products of light industry against increase oncological and nervous a disease and its influence on health of the person is discussed.